Analysis of E-Commerce Seller Behavior Using the Technology Acceptance Model (TAM) Method: : Case Study on the Thaijajan Community on Shopee - Rahayu, Resti; Khoiriyah, Rizqiyatul; Handhajani, S. B. P.; Indraswari, Ayu (Universitas Mohammad Husni Thamrin, 2025)
In Indonesia, there are various platforms that provide functions to carry out buying and selling transactions or called e-commerce. One of the e-commerce that is widely used in Indonesia is Shopee. Shopee is one of the e-commerce that is included in the B2C category that is widely used by people in various countries, especially in Indonesia. Shopee was officially launched for the first time in 2015 in Singapore and has expanded its business to other countries, such as Indonesia, the Philippines, Malaysia, Vietnam, Thailand, and Taiwan. The service provided by Shopee for sellers, namely Shopee Seller, is a reference for sellers and buyers when they are going to make buying and selling transactions using the Shopee application. There are several factors that must be owned by the Shopee Seller application which are benchmarks so that good and safe services are created when sellers make transactions. Therefore, it is necessary to conduct a behavioral analysis of sellers using the Technology Acceptance Model (TAM) method so that it can be known how users (sellers) behave towards accepting the e-commerce application used, namely Shopee Seller. This study was conducted on the THAIJAJAN seller community who use the Shopee Seller application using a descriptive approach. The results of the study show that the use and acceptance of the Shopee Seller application in the THAIJAJAN community are in the high category and have positive values. Thus, it is hoped that Shopee will always pay attention to the services and features provided so that they can satisfy the needs of Shopee users, especially for sellers.